Supressing loss channels in the bulk and at the surface of crystalline silicon solar cells - Zielke, Dimitri (2016)
Aluminum oxide, PEDOT:PSS/c-Si heterojunction, multicrystalline silicon, laser texture. - Aluminiumoxid, PEDOT:PSS/c-Si-Heteroübergang, multikristallines Silizium, Lasertextur